Prudent discounting: experimental evidence on higher-order time risk preferences - Ebert, Sebastian (SSRN, 2018)
We report results from an experiment that contrasts preferences toward the risk of what may happen (outcome risk preferences) with preferences toward the risk of when something may happen (time or delay risk preferences). Just as choices over monetary risks identify utility independently from discounting, choices over uncertain delays of a fixed reward identify discounting independently from utility. We replicate the widespread finding of outcome risk aversion, but — in a perfectly symmetric design — find substantial heterogeneity in delay risk aversion. Going beyond the second order of risk aversion, on the other hand, yields pervasive evidence for delay prudence and outcome prudence alike. This first empirical support for prudent discounting speaks to recent theoretical arguments that prudence may be a more important trait than previously realized
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments November 2, 2018 erstellt
Gesehen am 20.03.2023